COMMUNITY BASED TOURISM (CBT) DEVELOPMENT STRATEGY FOR NATURAL TOURISM OBJECTS IN CIAMIS REGENCY WEST JAVA - Irfan Nursetiawan; Intan Apriliani (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2020)
This research is motivated by the management of several natural tourism objects in Ciamis Regency based on Community Based Tourism, one of which is in the Jamiaki tourist attraction, Medanglayang Village, Panumbangan District, Ciamis Regency. Based on the results of research and observations in the field, the development of community-based tourism-based natural attractions in Jamiaki Tourism Object, Medanglayang Village, Panumbangan District, Ciamis Regency, is generally quite good. However, there are still indicators whose implementation is not appropriate in their implementation in the field. As for the obstacles faced in the tourism development strategy in Ciamis Regency, namely the presence of garbage brought by visitors to the tourist attraction sites, the education of the village community who has not yet reached a high level, the lack of time and consistent Human Resources (HR) In maintaining cohesiveness and working together, there are still some visitors who ignore the existing regulations, there is some egocentricity that emerged when the election of the head of tourism object management who did not comply with the rules to be wise in utilizing nature. Efforts to overcome the obstacles faced, namely educating the public to maintain the preservation of Natural Resources (SDA) at the location of Jamiaki tourist objects, building an understanding of diverse cultures and ways of life, namely by upholding tolerance in social life.